The dimensionality of the Behavior Rating Inventory of Executive Function, Second Edition in a clinical sample. Issue 4 (2nd October 2022) - Lace, John W.; Seitz, Dylan J.; Austin, Tara A.; Kennedy, Erin E.; Ferguson, Bradley J.; Mohrland, Michael D.
Abstract: The parent-report Behavior Rating Inventory of Executive Function, Second Edition (BRIEF-2) is a widely used pediatric neuropsychological measure. Unfortunately, despite meaningful changes from its predecessor, few studies have examined its internal factor structure (now with Behavioral Regulation [BRI], Emotion Regulation [ERI], and Cognitive Regulation [CRI]), and no available literature has investigated higher order models for the BRIEF-2. This study sought to address this shortcoming in the literature by investigating and reporting on the dimensionality of the parent-report BRIEF-2 in a clinical sample. Two hundred and two (202) pediatric neuropsychology examinees ( M age = 9.90; 68% males) with complete data for the parent-report BRIEF-2 were included. Descriptive results revealed generally elevated scores across BRIEF-2 scales (Global Executive Composite M T  = 70.16). Exploratory factor analyses suggested two factors (CRI and BRI/ERI) should be extracted, and that higher order models should be considered. Confirmatory factor analyses suggested that a direct hierarchical/bifactor two-factor structure (which was more parsimonious than the theoretical three-factor model) provided the best fit, with a bulk of the variance explained by the general GEC factor. The BRIEF-2 may be best interpreted at the overall level, with relatively less weight given to the index variables, particularly within clinical samples with high levels of reported executive functioning difficulties. Implications of these findings, limitations of the present study, and appropriate directions for future inquiry were discussed.